Enterprise risk management impact on performance of short-term insurance companies in Zimbabwe - Mahwe, Tendai (University of the Witwatersrand, Johannesburg, 2024)
Corporate failures that occurred in the mid-1990s, followed by the global financial crisis that began in the United States of America in 2007 and the 2008 hyperinflation period in Zimbabwe underscored the necessity for financial service providers in Zimbabwe to implement sound risk management practises and controls. Zimbabwe financial landscape, including the insurance sector was crippled as this affected the indemnification of policyholders. Regardless of the industry diversities, ERM is a significant factor to protect and increase shareholder value. Short term insurance companies are inherently more important in the financial services industry. Given that information, it was essential for the researcher to examine the impact of enterprise risk management in enhancing financial performance in the short-term insurance sector in a developing country like Zimbabwe. The review highlighted that Enterprise Risk Management (ERM) literature in the short- term insurance sector was mainly focused on developed countries, neglecting dynamic and developing countries like Zimbabwe. The study also revealed that Insurers in Africa are clustered with many risks that reduce their potential to thrive and increase capacity due to low penetration rates. Consequently, this study had to fill in this research gap and address enterprise risk management impact on performance in developing countries. Through following the quantitative approach, collecting, and analysing data through multiple regression model. Findings from the multiple regression analysis, established that financial performance in STIs’ is embedded in the effectiveness of enterprise risk management, firm size and leverage which were statistically significant with a p-value of 0.042, 0.015 and 0.034 respectively. The study suggested that the regulator must reinforce the capital requirements for insures and desist the one-size-fits all strategy to a risk-based approach as insurers underwrite different risks and industries. It is apparent that senior management must implement a holistic enterprise risk management program which can drive its financial performance in the market and lessen the possibility of failures.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Enterprise risk management; Risk; Short-term insurers; UCTD; SDG-8: Decent work and economic growth